Use of different matrix systems in the treatment of simple caries. - Kovács-Ivácson; Stoica Alexandra Mihaela; Pop Mihai; Dakó Timea ("George Emil Palade" University of Medicine, Pharmacy, Science, and Technology of Targu Mures, 2022)
Dental matrix systems are instruments used in the treatment of simple caries which replace the missing wall of the tooth during restoration. The aim of the study is to evaluate, using a questionnaire-based survey, the most used matrix systems among dentists and dentistry students. Materials and methods: Two hundred and fifty questionnaires containing 8 questions were distributed in electronic and printed format to dentists in Mureș and Harghita countries and dentistry students from 4th to 6th year of study at George Emil Palade University of Medicine, Pharmacy, Science, and Technology of Târgu Mureș. The obtained data were then analyzed using Microsoft Excel and SSPS 20.0.0. Statistical analysis was performed using the one tailed ANOVA and Tukey/ Kramer test. Significance level was set at a value of p<0.05. Results: Of the persons who completed the questionnaire 97.78% consider it important to use a matrix system during tooth restoration, 98.25 % use it when restoring class II Black cavities. Sectional matrixes are used most commonly during class II Black cavity restoration, for MOD cavities the circular matrix systems are the preferred ones. During class V Black cavity restoration only 5.45% of the doctors and students use a matrix system. Wooden wedge is used most frequently in combination with a matrix system. Only 3.3% always ask for a control X-ray after a tooth restoration. Conclusion: The use of matrix systems is considered to be very important by both dental students and dentists in the restoration of simple caries lesions and are most commonly used for a Black class II, III, IV, and MOD cavity. More importance should be given to follow-up X-rays after tooth restoration.